Faktor-Faktor Yang Mempengaruhi Minat Nasabah Non Muslim Melakukan Cicilan Emas Di Bank Syariah Indonesia KCP Kabanjahe - Fillia Anggita (Yayasan Rahmat Islamiyah, 2023)
This study aims to determine what factors influence the interest of non-Muslim customers in using gold installments. The analytical method used is quantitative analysis. This analysis includes: validity and reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The sample used in this study were 99 respondents. The results of the analysis show that there are three variables formed from four variables, namely, service, behavior, positive response and promotion. Which affects the interest of non-Muslim customers in using gold installments in Islamic banks.